Alternatif Desain Perkerasan Jalan dan Perkuatan Lereng Longsor - Asrul Saputra; Edy Purwanto; Miftahul Fauziah (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
This study aims to provide an alternative design for flexible pavement and slope reinforcemen. To simplify the analysis process, this research will use the Geo5 program, the Kenpave program, the Bina Marga 2017, the Fellenius method, and the Wedge method. The results of alternative 3 flexible pavement designs are AC-WC 4 cm, AC-BC 5 cm, AC Base 6 cm, and LFA Class A 40 cm, with a load repetition value of 2.363.985 ESAL until deformation damage occurs at a service life of 20 years. For the soil nailing slope reinforcement design, the safe factor value is 1.90 â‰¥ 1.30 for the Wedge method calculation, and the safety factor value is 1.34 â‰¥ 1.30 for the results of the Geo5 program.